KANDUNGAN NUTRISI SERAT BUAH KELAPA SAWIT YANG DIFERMENTASI DENGAN FESES KERBAU PADA LEVEL YANG BERBEDA - Jepri Juliantoni; Dewi Ananda Mucra; Dewi Febrina (Jurnal Peternakan, 2018)
This study was conducted from January to March 2013 in the Laboratory of Nutrition and Chemistry, Faculty of Agriculture and Animal Husbandry of the State Islamic University of Sultan Syarif Kasim Riau and analysis of the nutrient content in Ruminant Nutrition Laboratory of the Faculty of Animal Husbandry, Andalas University in Padang. This study aimed to determine the effect of buffalo feces with different levels of fermentation fruit oil palm fiber (SBKS) for 21 day against pH, fermentation quality, dry matter content, crude fiber, crude protein, ash and BETN. The method used in this study is completely randomized design with 4 treatments and 3 replications. The treatment given is the number of buffalo feces levels (0%, 10%, 20% and 30%). The results showed that the addition of up to 30% buffalo feces fermentation SBKS gave highly significant effect (P <0.0 l) on the pH, but not significant effect (P> 0.05) increase levels of dry matter, crude protein and BETN, and declining levels of crude fiber and crude fat levels.